2006
DOI: 10.1073/pnas.0603567103
|View full text |Cite
|
Sign up to set email alerts
|

Interlaced x-ray microplanar beams: A radiosurgery approach with clinical potential

Abstract: Studies have shown that x-rays delivered as arrays of parallel microplanar beams (microbeams), 25-to 90-m thick and spaced 100 -300 m on-center, respectively, spare normal tissues including the central nervous system (CNS) and preferentially damage tumors. However, such thin microbeams can only be produced by synchrotron sources and have other practical limitations to clinical implementation. To approach this problem, we first studied CNS tolerance to much thicker beams. Three of four rats whose spinal cords w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
214
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 175 publications
(229 citation statements)
references
References 48 publications
4
214
1
2
Order By: Relevance
“…This radioresistance phenomenon was not observed in 9L glioma microvessels, confirming the presence of a differential response to between normal and tumour brain tissues in rodents, an effect that can have significant clinical applications [19]. The neoplastic vasculature appears to be unable to replicate the fast repair of the segments hit by the peak dose, facilitating the development of radionecrosis over the irradiated tumor [12,20,28].…”
Section: Microbeam Radiosurgerymentioning
confidence: 72%
See 4 more Smart Citations
“…This radioresistance phenomenon was not observed in 9L glioma microvessels, confirming the presence of a differential response to between normal and tumour brain tissues in rodents, an effect that can have significant clinical applications [19]. The neoplastic vasculature appears to be unable to replicate the fast repair of the segments hit by the peak dose, facilitating the development of radionecrosis over the irradiated tumor [12,20,28].…”
Section: Microbeam Radiosurgerymentioning
confidence: 72%
“…Progressively lower doses (but still much higher than conventional radiosurgical or radiotherapeutic doses) are required to avoid tissue damage if ticker beams (100 to 600 gm) are used. Submillimetric beams (sized 0.6 to 0.7 mm) appear to retain the tissue sparing effect allowing to deliver incident doses of 400 Gy to the spinal cord of rats without inducing neurological damage: irradiation of rat spinal cord with four parallel 0.68-mm thick microbeams at 400 Gy in-depth beam dose did not induce paralysis after 7 months in three out of four rats [12]. This study showed not only that a highly radiosensitive structure such as the spinal cord can receive high dose irradiation through a microbeam array without neurologic sequelae but also that a beam width up to 0.68 mm is well tolerated, substantially maintaining the tissue sparing properties of thinner beams.…”
Section: The Tissue-sparing Effectmentioning
confidence: 99%
See 3 more Smart Citations